Digital Leadership in Strengthening Institutional Competitiveness: Evidence from an Islamic Higher Education Institution - Zulkhairi Zulkhairi; Abd Mukti; Mesiono Mesiono (Universitas Nurul Jadid, 2025)
This study examines the role of digital leadership in strengthening institutional competitiveness within higher education institutions. The rapid development of digital technology has encouraged universities to integrate digital systems into academic governance and service delivery, requiring leadership that is capable of guiding digital transformation strategically and responsibly. This research aims to explore how digital leadership contributes to institutional development through the understanding of digitalization, the implementation of digital strategies within the Tri Dharma of higher education, and the ethical governance of digital technologies. A qualitative case study approach was employed at IAIN Lhokseumawe to gain an in-depth understanding of leadership practices related to digital transformation. The findings reveal that leadership awareness of digitalization plays a crucial role in shaping institutional policies and strategies for the development of digital platforms. Digital initiatives have been integrated into various academic activities, including learning management, research administration, and community engagement programs. In addition, ethical leadership emerges as an important element in ensuring that digital technologies are implemented in a manner that emphasizes transparency, accountability, and equitable access. These findings highlight that digital leadership serves as a strategic mechanism for improving institutional coordination, enhancing academic services, and supporting the competitiveness of higher education institutions in an increasingly digital academic environment.